Conversational Agent for Industrial Processes through Virtual Environments. - Teneda Gallardo, Francisco Israel (2021)
. This paper presents the implementation of a conversational agent in virtual environments oriented to industrial control processes in order to contribute to the improvement of teaching-learning processes. The application simulates the level control process in two virtual environments, the first one as a virtual laboratory and the second environment as an industrial process. The environments have been created with three-dimensional models based on Piping and Instrumentation Diagram (P&ID) diagrams. The models have been simulated and animated using Unity 3D software. The environments exchange information in real time with MATLAB mathematical software to simulate the industrial process controller, achieving a high degree of realism. Each environment is assisted by a conversational agent who communicates with Dialogflow, a natural language understanding platform, to guide the user during their training. Test users were asked to provide feedback through a usability questionnaire, and these results are discussed at the end of this article.